Gastrojejunal Anastomosis Complications and Their Management after Laparoscopic Roux-en-Y Gastric Bypass - Yannick Fringeli; Marc Worreth; Igor Langer (Hindawi Limited, 2015)
Background. Complications at the gastrojejunal anastomosis after laparoscopic Roux-en-Y gastric bypass (LRYGB) are challenging in terms of diagnosis, therapy, and prevention. This study aims at identifying these complications and discussing their management. Methods. Data of 228 patients who underwent a LRYGB between October 2008 and December 2011 were reviewed retrospectively to evaluate the frequency and treatment of complications such as stenoses, marginal ulcers, perforated marginal ulcers, or anastomotic leaks related to the operation. Results. Follow-up information was available for 209 patients (91.7%) with a median follow-up of 38 months (range 24-62 months). Of these patients 16 patients (7.7%) experienced complications at the gastrojejunostomy. Four patients (1.9%) had stenoses and 12 patients (5.7%) marginal ulcers, one of them with perforation (0.5%). No anastomotic leaks were reported. One case with perforated ulcer and one with recurrent ulcers required surgical revision. Conclusion. Gastrojejunal anastomotic complications are frequent and occur within the first few days or up to several years after surgery. Stenoses or marginal ulcers are usually successfully treated nonoperatively. Laparoscopic repair, meanwhile, is an appropriate therapeutic option for perforated ulcers.